2005
DOI: 10.1103/physreve.71.041914
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of adult stem cells: Comparison of random and immortal-strand segregation mechanisms

Abstract: This paper develops a point-mutation model describing the evolutionary dynamics of a population of adult stem cells. Such a model may prove useful for quantitative studies of tissue aging and the emergence of cancer. We consider two modes of chromosome segregation: (1) Random segregation, where the daughter chromosomes of a given parent chromosome segregate randomly into the stem cell and its differentiating sister cell. (2) "Immortal DNA strand" co-segregation, for which the stem cell retains the daughter chr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This laboratory provided the first quantitative modeling of the potential effect of nonrandom segregation on DSC genetic fidelity [3]. It was estimated to afford a 100‐ to 1,000‐fold reduction in DSC mutation rate, but ideally to require suspended DNA repair [5], as suggested earlier [6, 7]. We also confirmed that nonrandom segregation occurs specifically during asymmetric self‐renewal [8, 9] as originally envisioned [2].…”
Section: Introductionsupporting
confidence: 83%
“…This laboratory provided the first quantitative modeling of the potential effect of nonrandom segregation on DSC genetic fidelity [3]. It was estimated to afford a 100‐ to 1,000‐fold reduction in DSC mutation rate, but ideally to require suspended DNA repair [5], as suggested earlier [6, 7]. We also confirmed that nonrandom segregation occurs specifically during asymmetric self‐renewal [8, 9] as originally envisioned [2].…”
Section: Introductionsupporting
confidence: 83%
“…Motivated by the immortal strand hypothesis [ 59 ] and non-random DNA strand co-segregation [ 60 ] we model mutation events in the malignant subpopulation of CSCs during symmetric division ( Fig. 5C ).…”
Section: Methodsmentioning
confidence: 99%
“…Given the constant demand for proliferation and the error-prone nature of DNA replication, these cells possess a high risk for malignant transformation [3] . As a consequence, it has long been postulated that ASCs might have acquired specialized features to protect their genome [4] , [5] . A highly efficient DNA-repair system is commonly described as a stem cell trait, which would serve this purpose [2] .…”
Section: Introductionmentioning
confidence: 99%